Fish as Hosts of Vibrio cholerae - Halpern, Malka; Izhaki, Ido (Frontiers in Microbiology, 2017)
Vibrio cholerae, the causative agent of pandemic cholera, is abundant in marine and freshwater environments. Copepods and chironomids are natural reservoirs of this species. However, the ways V. cholerae is globally disseminated are as yet unknown. Here we review the scientific literature that provides evidence for the possibility that some fish species may be reservoirs and vectors of V. cholerae. So far, V. cholerae has been isolated from 30 fish species (22 freshwater; 9 marine). V. cholerae O1 was reported few cases. In most cases V. cholerae was isolated from fish intestines, but it has also been detected in gills, skin, kidney, liver and brain tissue. In most cases the fish were healthy but in some they were diseased. Nevertheless, Koch postulates were not applied to prove that V. cholerae and not another agent was the cause of the disease in the fish. Evidence from the literature correlates raw fish consumption or fish handling to a few cholera cases or cholera epidemics. Thus, we can conclude that V. cholerae inhabits some marine and freshwater fish species. It is possible that fish may protect the bacteria in unfavorable habitats while the bacteria may assist the fish to digest its food. Also, fish may disseminate the bacteria in the aquatic environment and may transfer it to waterbirds that consume them. Thus, fish are reservoirs of V. cholerae and may play a role in its global dissemination.